FACTORS INFLUENCING LAVA-SUBSTRATE HEAT TRANSFER AND IMPLICATIONS FOR THERMOMECHANICAL EROSION - Fagents S.A.; Greeley R. (My University, 2001)
We develop numerical simulations of basaltic lava flowing laminarly over a basalt substrate in order to examine the details of the lava dynamics and thermal boundary layers and to understand the implications for substrate heating. As the initial stage of a larger study of thermomechanical erosion in different planetary environments, we aim to understand why erosion occurs on Earth, why erosion features are not ubiquitous given the high temperatures involved, and whether it is a plausible mechanism for the formation of planetary channels such as lunar sinuous rilles and venusian canali. Here we confine our attention to terrestrial lavas with well-known properties and eruption parameters. With relatively simple computational fluid dynamic simulations, most closely representing tube-fed hawaiian basalts (for which erosion has been documented), we demonstrate the importance of incorporating several key factors in models of lava flow/substrate heat transfer, which have commonly been neglected in previous treatments. By addressing the interaction of the flow dynamics and heat transfer in the lava, our work suggests that the development of a temperature gradient in the base of the lava, even for undeveloped flow, has a significant influence on substrate temperature. The sensitivity of the lava-substrate interface temperature to the thermophysical properties of the lava and substrate suggests that a delicate balance is required for partial melting to occur. Thus, it might take weeks of continuous flow to initiate partial melting of the substrate at distances of several kilometers from the vent. These durations exceed the periods of stability typical of lava flowing in tubes; pauses, blockages, surges, and breakouts frequently disrupt the flow. However, natural irregularities in the flow dynamics or substrate topography might help to initiate and maintain substrate melting on shorter timescales by disturbing the intimately coupled dynamic and thermal boundary layers. Although a purely thermal mechanism cannot be ruled out, our findings support the premise that mechanical erosion may play a key role in reports of erosion based on field evidence.
Keywords: LAVA FLOWS; COMPUTATIONAL FLUID DYNAMICS; THERMAL EROSION; BASALT; LAVA TUBES; SINUOUS RILLES; NUMERICAL MODELING